Per- and poly-fluoroalkyl substances (PFAS) sensing: A focus on representatively sampling soil vadose zones linked to nano-sensors - Bin Qian; John L. Rayner; Greg B. Davis; Adrian Trinchi; Gavin Collis; Ilias (Louis) Kyratzis; Anand Kumar (Ecotoxicology and Environmental Safety, 2024)
Per- and poly-fluoroalkyl substances (PFAS) are a group of organo-fluorine compounds that have been broadly used in consumer and industrial products spanning virtually all sectors. They can be found as surfactants, coatings and liners, polymer additives, fire retardants, adhesives, and many more. The chemical stability of the carbon fluorine bond and amphiphilic nature of PFAS result in their persistence and mobility in the environment via soil porewater, surface water and groundwater, with potential for adverse effects on the environment and human health. There is an emergent and increasing requirement for fast, low-cost, robust, and portable methods to detect PFAS, especially in the field. There may be thousands of PFAS compounds present in soil and water at extremely low concentration (0.01–250 ppb) that require measurement, and traditional technologies for continuous environmental sensing are challenged due to the complexity of soil chemistry. This paper presents a comprehensive review of potentially rapid PFAS measurement methods, focused on techniques for representative sampling of PFAS in porewater from contaminated soil, and approaches for pre-treatment of porewater samples to eliminate these interferences to be ready for PFAS-detecting sensors. The review discusses selectivity, a key factor underlying pre-treatment and sensing performance, and explores the interactions between PFAS and various sensors. PFAS chemical nano-sensors discussed are categorized in terms of the detection mechanism (electrochemical and optical). This review aims to provide guidance and outline the current challenges and implications for future routine PFAS sensing linked to soil porewater collection, to achieve more selective and effective PFAS sensors.